1989
DOI: 10.7863/jum.1989.8.3.135
|View full text |Cite
|
Sign up to set email alerts
|

Renal blood flow pattern by noninvasive Doppler ultrasound in normal children and acute renal failure patients.

Abstract: A pilot study of the Doppler renal arterial flow pattern was done in a group of 38 normal children, including 11 neonates age 2 weeks or less, 10 infants age 2 weeks to 1 year, and 17 children age 1 year and over. The appearance time, acceleration time, end-diastolic to peak-systolic velocity ratio (d/S), and diastolic to systolic flow ratio (A2/A1) increased with age. Another four patients with acute renal failure showed a characteristic absence of blood flow in the whole or late-diastolic phase. Diastolic fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 2 publications
2
20
0
1
Order By: Relevance
“…The Doppler indices recorded here--which are thought to reflect resistance and pulsatility of the vessels--might, therefore, have been expected to show similar changes. In addition, similar changes with age have been shown in studies carried out in healthy children of different age groups [16,17].…”
Section: [] Risupporting
confidence: 59%
“…The Doppler indices recorded here--which are thought to reflect resistance and pulsatility of the vessels--might, therefore, have been expected to show similar changes. In addition, similar changes with age have been shown in studies carried out in healthy children of different age groups [16,17].…”
Section: [] Risupporting
confidence: 59%
“…28 Several investigations of the renal BFV and RI in children, including a small group of infants during the first year of life, have been performed in cross-sectional studies. 7,[15][16][17] We showed a steady increase of the renal BFV in the same group of healthy infants during the first months of life. Renal physiologic development might explain the observation.…”
Section: -14mentioning
confidence: 78%
“…13,14 Cross-sectional studies of the BFV in renal arteries have also been performed in infants older than 30 days. 7,[15][16][17] To our knowledge there have been no studies looking at the normal preprandial splanchic BFV in infants older than 1 month. …”
mentioning
confidence: 99%
“…Earlier studies reported elevated renal vascular impedance with chronic hypertension (Norris et al, 1989) and acute renal failure (Wong et al, 1989). The intrarenal PI and RI would appear to be closely related to renal hemodynamic parameters and creatinine clearance in patients with chronic renal failure and hypertension (Petersen et al, 1995).…”
Section: Renal Medical Diseasesmentioning
confidence: 88%